Away - Chuang, Yu Hsin (2016)
Away is a short animated film following a boy, who lives in a world that was destroyed by air pollution caused by mankind. This, however, is the underlying message of our project, as we tell the story of our protagonist who goes on an adventure to break out of his comfort zone in search for nature. This report will cover the making-of process for Away, from its pre-production, production, post-production stages, to the final publicity aspect. It also aims to discuss the challenges that we faced and how we overcome them during our one year exploration.